Severe health shocks and financial well-being - Kaveh Majlesi; Elin Molin; Paula Roth (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2024)
We examine the effect of fatal and nonfatal health shocks on household debt defaults. Fatal shocks significantly cause defaults, especially among surviving spouses lacking sufficient resources, namely housing wealth. Our findings suggest that this behavior is not due to inattention. These shocks also have intergenerational consequences, as children of resource-poor surviving spouses become more likely to face debt collection. These findings in a country with a relatively generous welfare system manifest the graveness of background risks among poorer households and suggest the potential for improving social insurance programs. Nonfatal health shocks lead to an immediate but temporary increase in default likelihood.
Keywords: I12; G51; G22; 330; Financial Distress; Health Shocks; Household Debt; Household Saving